Evaluasi Usability dan Rekomendasi Perbaikan Tampilan Aplikasi IBI Library menggunakan Metode Usability Testing - Muhammad Rifqi; Hanifah Muslimah Az-Zahra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In the era of globalization, Bank Indonesia has created services that can support educational needs in Indonesia, one of which is the application of a digital library called iBI Library. The iBI Library application provides benefits to the public in reading books wherever they are without having to go and search for books in the library. Feedback from some users complained that there were some problems such as difficulty in finding features to register an account, some buttons that were unresponsive, and features that were less familiar to users. Therefore, it is necessary to evaluate the usability value in this application through 3 stages: initial evaluation to measure learnability, efficiency, error and satisfaction survey using LEMTool to measure satisfaction components, the second stage is making recommendations for improvement based on problems found through observation and interview, the third stage is to carry out further evaluation of the results of improvements that have been made based on a number of combined guidelines and then compared the value of the initial evaluation and further evaluation. The test participants who were respondents were library visitors (users) who were users who had the character of leisure or necessity factor, namely merely filling their free time and Subject of study, which meant having the subject of the field being explored. Overall, the improvement recommendations that have been made provide an increase in the value of the learnability component with a value of 71.45% to 91.62%, an increase in the value of the efficiency component with a value of 0.04 goals / sec to 0.07 goals / sec, a decrease in the value of the error component with a value of 17.5 % to 2.8%, and improvement in quality of satisfaction with an average value of positive emotions of 54.8% and negative emotions of 45.2% to 97.6% and negative emotions of 2.4% after improvement.